Enthalpy relaxation of the glassy matrix in vanadium–molybdenum–tellurite oxide glasses - Cardillo, Evangelina Cinthia (2013)
In this paper, we analyze using differential scanning calorimetry (DSC) how a disordered structure, obtained by the quenching of oxides melted into glass, is related to the nature of the modi- fier cation. We estimated the enthalpy relaxation in based tellurite oxide glasses of formula xM2O (1−x)(0.5 V2 O5 ·0.5MoO3 ) 2TeO2 when they are modified with univalent metal oxides as Na+ , Li+ and Ag+. As ionic conductors in tellurite oxide glasses, these cations have the same charge but different size, electronic configuration and, in addition, their electric behavior is quite different. We show that the jump in the Cp at Tg is also related to the nature of the modifier cation. We study the conventional view of the configurational entropy of liquid that is frozen below the glass transition temperature (Tg) with what is called entropy loss. We explore whether or not there is a relationship between the nature of the modifier oxide and its magnitude.